Improving Pulmonary Function and Functional Ability through Pulmonary Rehabilitation in Patients with Pleural Effusion: A Literature Review - Nazir, Arnengsih; Anggraini, Gabriella; Clementius, Brandon; Nurhalizah, Hana Athaya; Sutiono, Agung Budi (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Pleural effusion (PE) is characterized by reduced lung distensibility and expansion, resulting in decreased lung volume. Pleural effusion patients often experience respiratory symptoms that impair quality of life (QoL) and daily activities. Pulmonary rehabilitation (PR) has been developed to enhance functional capacity, alleviate symptoms, improve exercise tolerance, and reduce health service utilization. However, data on the specific implementation and benefits of PR in PE patients are limited. Methods: This literature review synthesized data from a search using Public Medline (PubMed), Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Google Scholar databases. The search was based on keywords relevant to study objectives and comprised various article types, ranging from review papers to original research. Articles with titles and abstracts relevant to the study objectives proceeded to a full-text evaluation. Results: A narrative review discussing PE from pathology to rehabilitation management was formulated from 12 articles that elucidated various aspects of functional impairment in PE patients and 24 sources that discussed rehabilitation management. Conclusion: Rehabilitation interventions, especially mobilization programs and lung expansion techniques, have shown effectiveness in improving pulmonary function and functional activities. Data regarding the role of inspiratory muscle training and aerobic exercise specific to PE remain limited. Given the functional impairments associated with PE, both before and after the removal of pleural fluid, PR programs are crucial in improving symptoms, pulmonary function, and overall functional ability in these patients.